Brilliant Light in Life and Material Sciences - Tsakanov, Vasili; Wiedemann, Helmut (Nato Security through Science Series B, Physics and Biophysics, 2007)
A NATO Advanced Research Workshop on "Brilliant Light Facilities and Research in Life and Material Sciences" was held from July 17 to July 21, 2006. The workshop was hosted by the Center for the Advancement of Natural Discoveries using Light Emission, Yerevan - the newly established institute in Armenia with the aim to create a synchrotron radiation facility, CANDLE, as an international laboratory for advanced research in life and material sciences. About 50 researchers from NATO, partner countries and Armenia gathered at Yerevan to discuss modern trends in developments of advanced light sources with high spectral brilliance and applications in basic and applied research in a wide range of fields. Research with high brilliant photon beams are used, for example for practical applications in pharmacy, electronics and nanotechnology. Such practical relevance promoted the design and construction of now more than 50 such facilities worldwide. Overview and specialized talks on the status and highlights of newly constructed light sources (ALBA, SPEAR3, European XFEL Facility, Siberian Synchrotron Radiation Center, CANDLE), on instrumentation and development of experimental techniques, and frontier research in life and material sciences using synchrotron radiation have been presented. More than 60% of the program was devoted to application of synchrotron radiation in biophysics, biochemistry, biomedicine, material and environmental investigations. The workshop brought together scientists from a wide spectrum of research fields emphasizing the wide application and demand of synchrotron radiation and underlining the necessity of user involvement in the early design stages of a new project.